2016
DOI: 10.1590/1678-4162-8704
|View full text |Cite
|
Sign up to set email alerts
|

Growth and hematological responses of tambaqui fed different amounts of cassava (Manihot esculenta)

Abstract: Growth and hematological responses of tambaqui fed different amounts of cassava (Manihot esculenta) ABSTRACTTambaqui,Colossoma macropomum is a fish of primary importance in Brazilian aquaculture and in the Amazon region in particular. The aim of this work is to analyze the combined effects of physical training and levels of dietary cassava (Manihot esculenta) on the hematological parameters, food intake, conversion efficiency, growth ratio and swimming performance of this fish. A diet for tambaqui consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
4
14
0
1
Order By: Relevance
“…Thus, the use of agroindustrial byproducts, such as rice, as demonstrated in this study, can reduce production costs for tambaqui. This has already been demonstrated with the use of cassava (Aride et al, 2016) and camu camu (Myrciaria dubia HBK Mc Vaugh) (Aride et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, the use of agroindustrial byproducts, such as rice, as demonstrated in this study, can reduce production costs for tambaqui. This has already been demonstrated with the use of cassava (Aride et al, 2016) and camu camu (Myrciaria dubia HBK Mc Vaugh) (Aride et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Peach palm meal could also replace corn meal in diets for tambaqui fingerlings without hampering their growth (Mori-Pinedo, 1999). Cassava (Manihot esculenta) was also evaluated as a viable and cost-effective tambaqui diet component (Aride et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This species has great potential for aquaculture due to its husbandry and management qualities, such as good feed conversion, acceptance of artificial food, resistance to long periods of hypoxia and excellent meat quality (Saint-Paul, 1991;Melard et al, 1993;Graef, 1995;Aride et al, 2007). These factors have contributed to it becoming the main species cultivated in northern Brazil (Val et al, 2000;Aride et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Embora a região amazônica apresente abundância de recursos hídricos, a busca de estratégias para assegurar a sustentabilidade dos recursos pesqueiros perante a crescente demanda por espécies de alto valor comercial mostra-se como um objetivo para cientistas e gestores nesta última década (Pestana, Pie & Pilchowski, 2008;Aride et al, 2016;Medeiros, Aubin & Camargo, 2017).…”
Section: Introductionunclassified